Korean Language - Park, Jun Seok; Sung, Chae Min (Institut Terjemahan & Buku Malaysia, 2015)
This Korean language textbook for beginners consits of 10 chapters. Each chapter different themes of daily life such as self-introduction, indication, action, date and day of the week, studying, sightseeing, shopping, transportation and food